A mesoporous titanium dioxide nanocomposite material encapsulating iron oxyhydroxide and its application

Exosomes are captured by mesoporous titanium dioxide nanocomposites wrapped in iron hydroxyl oxide and used as electrode materials for electrochemical sensors, and the complexity and sensitivity of exosome separation and detection in the prior art are solved, and efficient and sensitive exosome detection is achieved.

CN119503893BActive Publication Date: 2025-04-11YANBIAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510091945.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-11
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The prior art has problems such as complex operation, long time consumption, expensive equipment, large differences between samples, low abundance exosome recovery, and difficulty in removing vesicles and impurities of completely different sizes in the separation and detection of exosomes. The sensitivity of electrochemical biosensors is not ideal, and complex signal amplification means are required.

Method used

Mesoporous titanium dioxide nanocomposite material wrapped in hydroxy iron oxide is used. The material is prepared by hydrothermal method and sol-gel method. It has a large specific surface area and adjustable pore size. The phosphate group can be combined with the phospholipid bilayer of the exosome. It can directly capture the exosome without modification. It is used as an electrode material for electrochemical sensors to enhance the charge transfer capability at the interface between the material and the electrolyte.

Benefits of technology

It realizes efficient capture of exosomes, enhances electrochemical signal response, simplifies the detection process, improves detection sensitivity and accuracy, and is suitable for the application of electrochemical sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503893B_ABST
    Figure CN119503893B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a mesoporous titanium dioxide nanocomposite material wrapped with iron oxyhydroxide, which comprises: FeOOH@mTiO 2 Nanocomposite preparation, FeCl 3 6H 2 O is a precursor, tetrabutyl titanate is a titanium source, and ammonia water is a pore regulator. As a nanocomposite material, it is used to capture exosomes and is combined with an electrochemical sensor to establish a method for quantitatively detecting exosomes. 2 Nanocomposites as electrode materials have enabled a simple and highly sensitive electrochemical sensor to quantitatively detect exosomes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation and relates to a mesoporous titanium dioxide nanocomposite material encapsulating iron oxyhydroxide and a use thereof. Background Art

[0002] Exosomes are tiny vesicles secreted by cells, with a diameter of They originate from cells and exist in a variety of body fluids, including serum, urine, saliva, milk, bile and other fluids. In recent years, exosomes have attracted widespread attention as intercellular communication carriers of nucleic acids, proteins and other biomolecules. In addition, they play an important role in many biological processes such as tumorigenesis, signal transduction and immune response. Moreover, exosomes can be transported and exchanged between cells and body fluids, and the intact vesicle structure of exosomes protects the contained biomarkers from degradation and enzymatic hydrolysis.

[0003] Studies have found that the release of exosomes has been found in many tumor cells, including liver cancer, ovarian cancer, breast cancer, prostate cancer, colorectal cancer, etc. In addition, compared with normal cells, tumor cells tend to release more exosomes. Tumor-derived exosomes can change vascular permeability, promote tumor metastasis and spread, and help cancer cells escape the clearance of the immune system. For example, exosomes can induce apoptosis of immune cells (Fas ligand in exosomes from prostate cancer and melanoma can induce apoptosis of T lymphocytes). In addition, exosomes secreted by tumor cells will also increase the drug resistance of tumors, because tumor cells can enhance their resistance to chemotherapy drugs by carrying resistance-related molecules, transmitting resistance information, and regulating apoptosis signaling pathways. Therefore, it is very necessary to diagnose early cancer in a timely manner through quantitative detection of exosomes. However, there are still many challenges in the separation and detection of exosomes. Although ultracentrifugation can provide exosomes with higher purity, its main disadvantages include complex operation, long time consumption, expensive equipment, large differences between samples, low recovery rate of low-abundance exosomes, and difficulty in removing vesicles and impurities of completely different sizes. These limitations affect the separation efficiency of exosomes and the feasibility of clinical application. Some electrochemical biosensors for quantitative detection of exosomes have been developed, but these sensors have the disadvantages of still not ideal sensitivity and the need for complex signal amplification methods, which limits their further application.

[0004] In recent years, nanomaterials have been widely used in the capture of exosomes due to their unique structural and functional properties at the nanoscale. The surface of nanomaterials can be modified with specific ligands, which can specifically recognize and bind to specific markers on the surface of exosomes, thereby achieving highly selective capture of exosomes; in addition, by controlling the size and structure of nanomaterials, they can match the size of exosomes and use size exclusion or sieving principles to achieve selective capture of exosomes; and nanomaterials usually have a higher specific surface area, which means that more active sites can be used to interact with exosomes to improve capture efficiency.

[0005] The present invention prepares a Nanocomposite material. The outer layer of this composite material It will bind bidentately to the phosphate groups on the phospholipid bilayer of exosomes to enrich exosomes. It can directly capture exosomes without modification, and its mesoporous characteristics give it a large specific surface area and more active sites. and The interfacial interaction between the electrolyte and the material will improve the charge transfer capacity at the interface of the electrochemical biosensor and enhance the electrochemical signal. Nanocomposites are well suited for other biomedical applications including the construction of electrochemical biosensors. Summary of the invention

[0006] The purpose of the present invention is to provide a mesoporous titanium dioxide nanocomposite material encapsulating iron oxyhydroxide in view of the deficiencies of the prior art.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] A mesoporous titanium dioxide nanocomposite material encapsulating iron oxyhydroxide, wherein the nanocomposite material requires three steps to prepare: a core synthesized by a hydrothermal method; , the intermediate was synthesized by sol-gel method , synthesized by hydrothermal method Nanocomposite materials.

[0009] Furthermore, the The precursors required for the preparation of ;

[0010] Said The preparation method comprises:

[0011] Pick Add deionized water and mix, then heat in an oil bath to obtain the desired Nanoparticles;

[0012] The temperature of the heating reaction is ;

[0013] The heating reaction time is .

[0014] Furthermore, the The titanium source tetrabutyl titanate required for the preparation;

[0015] Said The preparation method comprises:

[0016] Pick Add to a mixed solvent of anhydrous ethanol and acetonitrile and mix, continue to add alkali solution and mix, and ultrasonicate to obtain a uniform solution;

[0017] Add tetrabutyl titanate under stirring to obtain the desired Nanoparticles;

[0018] The alkali solution includes an aqueous ammonia solution;

[0019] The stirring rate is .

[0020] Furthermore, the Ammonia water is a pore regulator required for the preparation;

[0021] Said The preparation method comprises:

[0022] Pick Add anhydrous ethanol and deionized water to the mixed solvent and continue to add alkali solution to mix. Move the resulting uniform solution to a reactor and heat it to obtain the desired Nanoparticles;

[0023] The alkali solution includes an aqueous ammonia solution;

[0024] The temperature of the heating reaction is ;

[0025] The heating time is .

[0026] Furthermore, the Parameters of nanoparticles include: surface area , average pore size , average pore size .

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] The present invention provides a mesoporous titanium dioxide nanocomposite material encapsulating iron oxyhydroxide, wherein the mesoporous structure has the advantages of large specific surface area, adjustable pore size, stable physical and chemical properties, etc. The phosphate groups on the surface of the exosomes will bind to the bidentate of the phospholipid bilayer of the exosomes, and the exosomes can be directly captured without modification.

[0029] Another object of the present invention is to provide a mesoporous titanium dioxide nanocomposite material encapsulating iron oxyhydroxide for use as an electrode material for an electrochemical sensor in detecting exosomes. and The interfacial interaction on the surface can enhance the charge transfer effect at the interface between the material and the electrolyte, enhance the electrochemical response current, and play a role in the application of electrochemical sensors as detection of exosomes.

[0030] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0031] A mesoporous titanium dioxide nanocomposite material encapsulating iron oxyhydroxide is used as an electrode material for an electrochemical sensor for detecting exosomes.

[0032] Further, comprising the step of adding a selected amount of said Steps to combine with electrodes:

[0033] Take the selected amount of The nanocomposite material was dropped onto the surface of the glassy carbon electrode, dried in an oven, and then allowed to cool to room temperature;

[0034] The drying temperature is ;

[0035] The drying time is ;

[0036] A material electrode is formed.

[0037] Furthermore, the steps of combining the material electrode with serum to detect exosomes are as follows:

[0038] Selected amounts of normal serum samples, liver cancer serum samples, and colon cancer serum samples were dropped onto the surface of the material electrode, dried at room temperature, and then rinsed with PBS for electrochemical detection;

[0039] The exosome concentrations of normal serum samples, liver cancer serum samples, and colon cancer serum samples were calculated based on the obtained data.

[0040] Compared with the prior art, the present invention has the following advantages:

[0041] The present invention provides a mesoporous titanium dioxide nanocomposite material wrapped with iron oxyhydroxide, which is used as an electrode material of an electrochemical sensor and is used in detecting exosomes. The mesoporous structure has the advantages of large specific surface area, adjustable pore size, stable physical and chemical properties, etc. The phosphate groups on the surface of the exosomes will bind to the bidentate of the phospholipid bilayer of the exosomes, and the exosomes can be directly captured without modification. and The interfacial interaction on the surface can enhance the charge transfer effect at the interface between the material and the electrolyte, enhance the electrochemical response current, and play a role in the application of electrochemical sensors as detection of exosomes. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 for Morphological characterization. (a) Scanning electron microscope (SEM) image; (b) Scanning electron microscope (SEM) image; (c) Scanning electron microscope (SEM) image; (d) Transmission electron microscope (TEM) image; (e) Transmission electron microscope (TEM) image; (f) Transmission electron microscopy (TEM) image of .

[0043] Figure 2 for Nitrogen adsorption-desorption curve and pore size distribution diagram.

[0044] Figure 3 for XRD characterization.

[0045] Figure 4 For different concentrations Impact on sensing performance.

[0046] Figure 5 for Sensor detection of different concentrations of exosomes derived from liver cancer cell line (Huh7) (a) CV; (b) EIS; (c) DPV; (d) linear relationship between the logarithm of exosome concentration and the change in DPV peak current.

[0047] Figure 6 for The sensor quantitatively detected the exosome concentration in the serum of liver cancer patients, colon cancer patients and healthy people. DETAILED DESCRIPTION

[0048] The present invention is specifically described as a mesoporous titanium dioxide nanocomposite material encapsulating iron oxyhydroxide and its use;

[0049] The core was synthesized by hydrothermal method. , synthesized by sol-gel method , synthesized by hydrothermal method Nanocomposite materials.

[0050] Synthesized by hydrothermal method Nanocomposites, selection of precursors: , titanium source: tetrabutyl titanate, pore regulator: ammonia water.

[0051] Synthetic Nanocomposites were used as electrode materials to develop electrochemical sensors for detecting exosomes.

[0052] The above method specifically comprises the following steps:

[0053] (1) Preparation: Weigh a certain amount of Dissolve in deionized water and heat in an oil bath; centrifuge and wash the resulting product several times, and then dry it to obtain .

[0054] (2) Preparation: Weigh a certain amount of The nanomaterials are uniformly dispersed in a mixed solution of anhydrous ethanol and acetonitrile, and Solution, ultrasonic dispersion , tetrabutyl titanate (TBOT) is added dropwise under continuous stirring, the resulting product is centrifuged and washed several times, and then dried to obtain ;

[0055] (3) Preparation: Weigh a certain amount of The nanomaterials were evenly dispersed in a mixed solution of anhydrous ethanol and deionized water, and ultrasonically dispersed ,join in solution; after mixing evenly, transfer the solution to a high-pressure hydrothermal reactor; centrifuge the obtained product, wash it several times, and dry it to obtain .

[0056] Further, to explore the material concentration detected by subsequent exosome electrochemical sensors, we selected The electrochemical performance of the materials was tested.

[0057] Further, coated with The glassy carbon electrode is used as the working electrode. The reference electrode, the Pt electrode as the auxiliary electrode, and potassium ferrocyanide as the electrolyte are constructed. Electrochemical sensor.

[0058] Further, in the coating Different concentrations of liver cancer exosomes ( Cell line-derived exosomes), dried at room temperature, and then the standard curve was determined.

[0059] Further, in the coating The serum of liver cancer patients, colon cancer patients and healthy people was added to the glassy carbon electrode. After rinsing with PBS, the exosome concentrations in the serum of liver cancer patients, colon cancer patients and healthy people were calculated by converting the peak current and the exosome concentration.

[0060] Parameter settings for three electrochemical detection methods:

[0061] (1) Cyclic voltammetry (CV): Voltage range: , scan rate: , sampling interval: , sensitivity: .

[0062] (2) Electrochemical impedance spectroscopy (EIS): High frequency: , starting voltage: open circuit voltage, amplitude: .

[0063] Differential Pulse Voltammetry (DPV): Voltage Range: , pulse width: , sampling width: , pulse period: , sensitivity: .

[0064] Example 1 Preparation

[0065] 1. Preparation

[0066] Preparation: Measure Deionized water is placed in a round-bottom flask, a thermometer is inserted into the round-bottom flask, and the oil bath is heated to a temperature of , keep the heating temperature unchanged, take out the round-bottom flask and thermometer, and dry the round-bottom flask in an oven.

[0067] Weigh of In the above dried round-bottom flask, add Deionized water, shake until Completely dissolve in deionized water.

[0068] Make sure the liquid level of the round-bottom flask is completely immersed in the preheated oil bath in the preparation work. ,reaction .

[0069] After the reaction is completed, pour the solution in the round-bottom flask into In centrifuge tube, After centrifugation, the product was washed with deionized water three times and anhydrous ethanol three times.

[0070] Finally, the product After drying, you can get .

[0071] 2. Preparation

[0072] Weigh of In a beaker, add Anhydrous ethanol and Acetonitrile, then pipette of of , mix well.

[0073] The mixture was ultrasonically ,to Completely dispersed in solution.

[0074] Add magnets to the beaker and slowly pipette of ,exist Add dropwise under continuous stirring , reaction at room temperature .

[0075] After the reaction is completed, pour the solution in the beaker into In centrifuge tube, After centrifugation, the product was washed with anhydrous ethanol three times and acetonitrile three times.

[0076] Finally, the product After drying, you can get .

[0077] 3. Preparation

[0078] Weigh of In a beaker, add Anhydrous ethanol and Deionized water, mix well.

[0079] The mixture was ultrasonically ,to Completely dispersed in solution.

[0080] Pipette suction of of , shake until the solution is mixed evenly.

[0081] Transfer the resulting homogeneous solution to a volume of Teflon-lined stainless steel autoclave, Heating reaction .

[0082] After the reaction was completed, the reactor was taken out and cooled to room temperature.

[0083] Pour the solution in the reactor into In centrifuge tube, After centrifugation, the product was washed with anhydrous ethanol three times and deionized water three times.

[0084] Finally, the product After drying, you can get .

[0085] Example 2: Sensor Sensing Performance Study

[0086] (1) Prepare materials of different concentrations: weigh of ,join in Deionized water and Nafion solution, sonication until the material is completely dispersed in the solution.

[0087] (2) Prepare electrolyte: of , Potassium ferrocyanide ( ), Potassium ferrocyanide ( ), dissolved in In deionized water, shake the solution evenly and wrap the bottle with a layer of tin foil to protect it from light.

[0088] (3) Pretreatment of glassy carbon electrode: First, use and of The surface of the glassy carbon electrode was polished with powder and then ultrasonically cleaned with ethanol and deionized water respectively. , remove the residual The powder is then rinsed with deionized water to remove contaminants.

[0089] (4) Grinding the electrode: Take a small amount Polishing powder ( ) on the grinding disc, then add a small amount of deionized water, hold the glassy carbon electrode vertically, and apply force evenly with your elbow to move the glassy carbon electrode slowly on the surface of the grinding disc in an "8" shape. During the grinding process, ensure that the electrode surface is pressed against the grinding disc and cannot be skewed.

[0090] (5) Take Different concentrations ( ) The dispersed solution of the material is dripped onto the glassy carbon electrode prepared in step (4) and placed in an oven Dry, and finally place the electrode at room temperature to room temperature.

[0091] (6) Pour two-thirds of the electrolyte into the electrolytic cell, insert the working electrodes of different concentrations prepared in step (5) into the electrolytic cell, and then put Reference electrode and Electrode for electrochemical detection. Figure 4 As shown, when the material concentration is When , the peak value of DPV response current reaches the highest.

[0092] (7) Differential pulse voltammetry (DPV) electrochemical experiments were performed in an electrochemical workstation CHI760E at a temperature of The prepared The electrode is the working electrode and the reference electrode is , the auxiliary electrode is The scanning rate of the electrode is , the scanning voltage is , the sensitivity is (The above conditions were used in the subsequent electrochemical experiments of cyclic voltammetry (CV), differential pulse voltammetry (DPV) and impedance spectroscopy (EIS).

[0093] Example 3 Establishment of standard curve

[0094] Under the optimal analytical conditions, cyclic voltammetry, differential pulse voltammetry and electrochemical impedance spectroscopy were used to detect different concentrations of liver cancer exosomes (exosomes derived from Huh7 cell line), respectively.

[0095] Add a drop of of of , placed in an oven drying.

[0096] After the mixture is cooled to room temperature, add Different concentrations ( ) exosomes.

[0097] After drying at room temperature, the sections were rinsed three times with PBS.

[0098] The measured results are as follows Figure 5As shown in abc, with the increase of exosome concentration, the redox peak of CV gradually weakened, the radius of curvature of EIS increased, and the electrochemical signal response of DPV gradually weakened, which all indicate that after the sensor captures the exosomes, it hinders the charge transfer on the surface of the material, the redox ability of the material weakens, the resistance increases, and the conductivity deteriorates. Among the three electrochemical methods, differential pulse voltammetry showed better sensitivity, so the logarithmic value of the exosome concentration was used as the horizontal axis (represented by the variable x), and the difference between the DPV peak value of exosomes of different concentrations and the DPV peak current of the blank sample was taken as the vertical axis (represented by the variable y) to establish a standard curve. Figure 5 d, the established linear equation is , has a good linear relationship, indicating that the use of The sensor is feasible for detecting exosomes, and the actual detection limit is .

[0099] Example 4 Detection of serum exosomes

[0100] Serum samples from patients with clinical liver cancer, patients with clinical colon cancer and normal people were analyzed under the same conditions as above. After sensor detection, the electrochemical peak current obtained was converted into exosome concentration based on the established linear relationship.

[0101] Figure 6 yes The sensor tested the serum of liver cancer patients, colon cancer patients and normal people. The serum of liver cancer patients and colon cancer patients contained more exosomes than that of normal people, and there was a significant difference ( ), which is statistically significant. The sensor provides new possibilities for early diagnosis by quantitatively detecting exosomes to differentiate cancer patients from normal people.

[0102] The above technical solutions only reflect the preferred technical solutions of the technical solutions of the present invention. Some changes that may be made to certain parts thereof by technicians in this technical field all reflect the principles of the present invention and fall within the protection scope of the present invention.

Claims

1. A use of a mesoporous titanium dioxide nanocomposite material encapsulating iron oxyhydroxide in detecting exosomes, characterized in that: The nanocomposite material is used as an electrode material for an electrochemical sensor to detect exosomes. The nanocomposite material requires three steps to prepare: synthesizing the core FeOOH by a hydrothermal method, synthesizing the intermediate FeOOH@TiO2 by a sol-gel method, and synthesizing the FeOOH@mTiO2 nanocomposite material by a hydrothermal method; The preparation method of the FeOOH comprises: Take FeCl3·6H2O, add deionized water and mix, and heat in an oil bath to obtain the desired FeOOH nanoparticles; The heating temperature is 60-80°C; The heating time is 4-6h; The preparation method of the FeOOH@TiO2 comprises: Take FeOOH and add it to a mixed solvent of anhydrous ethanol and acetonitrile, then add ammonia solution and mix, and perform ultrasonication to obtain a uniform solution; Tetrabutyl titanate is added under stirring to obtain the desired FeOOH@TiO2 nanoparticles; The stirring rate is 350-450r / min; The preparation method of the FeOOH@mTiO2 comprises: Take FeOOH@TiO2 and add it to a mixed solvent of anhydrous ethanol and deionized water, and then add ammonia solution to mix. Move the obtained uniform solution to a reactor and heat it to obtain the desired FeOOH@mTiO2 nanoparticles. The heating temperature is 150-200°C; The heating time is 20 hours.

2. The use of the mesoporous titanium dioxide nanocomposite material encapsulating iron oxyhydroxide according to claim 1 in detecting exosomes, characterized in that: The parameters of the FeOOH@mTiO2 nanoparticles include: specific surface area 100-140m 2 .g -1 , average pore size 3.0-3.5nm, average pore volume size 0.6-0.7cm 3 .g -1 .

3. The use of the mesoporous titanium dioxide nanocomposite material encapsulating iron oxyhydroxide according to claim 1 in detecting exosomes, characterized in that: The method comprises the steps of combining a selected amount of the FeOOH@mTiO2 with an electrode: A selected amount of the FeOOH@mTiO2 nanocomposite material is dropped onto the surface of a glassy carbon electrode, dried in an oven, and then cooled to room temperature to form an electrode material; The drying temperature is 50-70°C; The drying time is 5-10 minutes.

4. The use of the mesoporous titanium dioxide nanocomposite material encapsulating iron oxyhydroxide according to claim 3 in detecting exosomes, characterized in that: The steps of combining the electrode material with serum to detect exosomes are as follows: Selected amounts of normal serum samples, liver cancer serum samples, and colon cancer serum samples were dropped onto the surface of the electrode material, dried at room temperature, and then rinsed with PBS for electrochemical detection; The exosome concentrations of normal serum samples, liver cancer serum samples, and colon cancer serum samples were calculated based on the obtained data.

Citation Information

Patent Citations

  • One-dimensional alpha-FeOOH / TiO2 composite photocatalyst, hydrothermal synthesis method and application

    CN115007149A

  • Separation and detection method and application of exosome

    CN116577403A